Opinion of Residents on Lighting in the City of Pila - Gorzelańczyk, Piotr; Miśkowski, Miłosz (Olsztyn Economic Journal, 2022)
The article analyzes the efficiency of street lighting in the city of Pila. For this purpose, a survey was conducted to find out the opinions of residents about lighting in the city of Pila. For this purpose, 167 residents of Pila were asked what they thought about lighting in the analyzed city. Based on the survey, some of the respondents believe that road lighting is good and effective, while the other part says that lighting does not fulfill its functions, tasks and something should be changed in this regard. There are several streets that are well and poorly lit at the same time, so the effectiveness of street lighting in these places cannot be clearly determined. There is also a group of respondents who indicate that the lighting does not work properly, i.e. it is out of order for a long time. The last part of the article contains suggestions for upgrading city lighting in Pila. The article ends with a summary.